Strengthening Nationalism and Insight in Kenteng Youth through Pancasila-Based Street Law Education: Penguatan Nasionalisme dan Wawasan Melalui Street Law Education Berbasis Pancasila untuk Pemuda Desa Kenteng - Arifin, Ridwan; Wedhatami, Bayangsari; Alkadri , Riska; Ananta, Bintang Rafli; Damayanti , Fitria; Baiquni, Muhammad Iqbal; Sari , Dewi Puspa; Herawan , Wahyu Nandang (Faculty of Law, Universitas Negeri Semarang, 2024)
Social transformation focusing on youth through Pancasila-based legal education has been implemented in Desa Kenteng using the Street Law model. This study aims to evaluate the effectiveness of this model in strengthening nationalism and national awareness among village youth. The Street Law method, which integrates Pancasila principles with legal theory and practice, is designed to enhance legal understanding while instilling national values in a local context. The results of the program indicate a significant increase in legal knowledge, with basic legal understanding rising from 30% to 75% after six months. Additionally, there was a substantial increase in nationalism and awareness of Pancasila values, from 40% to 85%, and a rise in social participation from 20% to 60% among village youth. Despite these positive outcomes, challenges such as uncertainty in practical legal application and the need for ongoing support from government and local legal institutions remain. This study recommends integrating national values into legal education policies and adapting program models to local contexts to ensure broader and sustainable impact in other regions.